1984
DOI: 10.1084/jem.159.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of IgD. IV. Enhancement of antibody production in mice bearing IgD-secreting plasmacytomas.

Abstract: Immune responses to trinitrophenylated hemocyanin (TNP-KLH), Ficoll (TNP-Ficoll), and Brucella abortus (TNP-BA) were examined in BALB/c mice bearing subcutaneous transplants of TEPC-1017 and TEPC-1033, the two known IgD-secreting BALB/c plasmacytomas. Both primary and secondary 19S and 7S splenic plaque-forming cell (PFC) responses in spleen to intravenously injected TNP-KLH were enhanced three to fivefold. Primary responses to TNP-Ficoll were 1.5-2 times higher than in control mice (particularly the 7S PFC re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…I). This was in marked contrast to results with plasmacytomas secreting other isotypes (Zolla-Pazner et al 1974, Xue et al 1984. We hypothesized that the immunoaugmentation resulted from the elevated serum IgD levels in the IgD plasmacytoma-bearing mice.…”
Section: Humoral Immunoaugmenting Effects Of Igdcontrasting
confidence: 66%
See 2 more Smart Citations
“…I). This was in marked contrast to results with plasmacytomas secreting other isotypes (Zolla-Pazner et al 1974, Xue et al 1984. We hypothesized that the immunoaugmentation resulted from the elevated serum IgD levels in the IgD plasmacytoma-bearing mice.…”
Section: Humoral Immunoaugmenting Effects Of Igdcontrasting
confidence: 66%
“…As in the case of IgD plasmacytoma-bearing mice, the immunoaugmenting effect of IgD pre-treatment was seen both in primary and secondary responses. Comparable results were obtained with affinity purified IgD (Xue et al 1984). In similar experiments with athymic BALB/c mice, however, IgD had no effect on the response to either T-dependent or T-independent antigens, suggesting a crucial role for T cells in the IgD-induced immunoaugmentation.…”
Section: Humoral Immunoaugmenting Effects Of Igdmentioning
confidence: 56%
See 1 more Smart Citation
“…All of these studies support the concept that IgD may act as a receptor and may regulate B cell differentiation. Recent work by Xue et al (28) demonstrated an enhanced 19s and 7s antibody response to keyhole limpet hemocyanin in mice bearing IgD-secreting plasmacytornas. The authors suggested the existence of an IgD responsive regulatory T cell.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin D (IgD) is a major antigen receptor isotype coexpressed with IgM on the surface of mature B lymphocytes in mice, humans, and other species. It has been demonstrated that IgD also serves as a ligand for IgD-specific receptors (IgD-R) expressed on CD4 ϩ T cells and that deglycosylated IgD fails to bind to these receptors [1][2][3][4][5]. Moreover, N-acetylgalactosamine blocks the binding of IgD-R to IgD-coated target cells, suggesting that IgD-R have lectin-like properties [6 -8].…”
Section: Introductionmentioning
confidence: 99%